2021
DOI: 10.1007/s12371-021-00616-1
|View full text |Cite
|
Sign up to set email alerts
|

Developing Culturally Effective Strategies for Chinese to English Geotourism Translation by Corpus-Based Interdisciplinary Translation Analysis

Abstract: As a new field of translation with its own special genre, geotourism has not yet been firmly established because geotourism translations are currently not of a sufficient professional standard. This situation does not provide geotourists with the genre’s full target of enjoyment, learning and engagement through science popularisation tourism activities. In order to better meet these three definitive purposes in geotourism, this study analyses the three basic categories of geotourism—geological features (GFs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…rough Pan's research, using data from the Translation Corpus, a corpus of learners developed for the study of lexical cohesion, through case studies, the results showed the complexity of a learner's language and its relationship to various factors such as learner, text, and task [1]. rough Li's research, some advantages of Hu's ecological translation theory were explained, the translation was used to minimize translation problems, and corpus linguistics method was used, which excels in quantitative and qualitative analysis [2]. Zhao et al aimed to explore how narrative space can be transferred from one language to another.…”
Section: Related Workmentioning
confidence: 99%
“…rough Pan's research, using data from the Translation Corpus, a corpus of learners developed for the study of lexical cohesion, through case studies, the results showed the complexity of a learner's language and its relationship to various factors such as learner, text, and task [1]. rough Li's research, some advantages of Hu's ecological translation theory were explained, the translation was used to minimize translation problems, and corpus linguistics method was used, which excels in quantitative and qualitative analysis [2]. Zhao et al aimed to explore how narrative space can be transferred from one language to another.…”
Section: Related Workmentioning
confidence: 99%
“…Many studies conducted in this field including ; An, J., & Sun, J. (2022), Curran, et al (2022), Francisco-Velilla, et al (2022, Ginting (2022), Hrytsanchuk (2022), Jameel (2022), Li, et al (2022), Saha and Mandal (2022), Giroux, et al (2021), Anber and Jameel (2020), Iglikova and Usataya (2019), and Leni and Pattiwael (2019), showed that using the appropriate translation strategy is the key of successful translation and delivering précis and accurate information in a scientific style. This study tries to enrich the Iraqi literature concerning the translation strategies that the EFL students use in translation and the quality of the translation from English into Arabic or vice versa.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Some scholars also believe that the key to mountain village tourism is to analyze the professional villages, analyze the areas where the professional villages gather, and find out the differences [ 6 ]. Some scholars believe that the personalization of mountain village tourism is obvious, and the reasons for its agglomeration should be analyzed [ 7 ]. Some scholars believe that applying the theory of system dynamics to mountain village tourism can find out the characteristics of mountain village tourism through the analysis of the driving factors of tourism.…”
Section: Literature Reviewmentioning
confidence: 99%